Effect of different dosages of zinc supplementation on nutritional status, aerobic and anaerobic performance in elite female volleyball players - Eskici, G. (South African Journal for Research in Sport, Physical Education and Recreation, 2021)
Zinc is an essential element for the performance of athletes. This study aims to determine the effect of two different dosages of zinc supplementation in elite female volleyball players on nutritional status, aerobic, anaerobic performance and fatigue. The research involved 20 female athletes who played in Gazi University Sports Club volleyball team. Subjects were divided into two groups equal in number. Different dosages of zinc sulphate were applied for four weeks: (1) Group 1 (220mg/day zinc sulphate; (2) Group 2 (440mg/day zinc sulphate). Athletes who were already engaged in their daily training routines were given a 20m-shuttle run test to create fatigue before and after supplementation. Also, a Wingate test was performed to determine the anaerobic power before and after the supplement. Zinc supplementation did not cause a significant change in both groups in both anaerobic and aerobic performance. However, zinc supplementation in both groups caused a substantial shift in plasma lactate levels (p<0.05). Pre- supplementation exercise elevates plasma lactate levels, while zinc supplementation led to a fall in plasma lactate. Zinc supplementation caused a significant increase in daily energy, protein, and fat intakes in both groups.